Reinterpretasi Ayat Pernikahan Beda Agama - Muhammad Roni; Muhammad Nasir (Hukum Keluarga Islam IAIN LANGSA, 2022)
God created human beings in pairs to complement each other between men and women. Marriage is the sunnah of the Prophet, and so much benefit occurs from a marriage bond. Furthermore, marriage is how it is said to be valid in Islam. Whether interfaith marriage is also part of a muslim's personal treasure. In order to answer this, the author uses the tahsis motto in expressing the opinion of Rasyid Ridha in his interpretation, and is also a supporter of several related articles. The results showed that interfaith marriage is an act that cannot be said to be valid even if there are texts (both books and scholarly thoughts), as for the reason because interfaith marriage is irrelevant to the dynamics of current life, especially in the frame of nation and state.